2013
DOI: 10.4028/www.scientific.net/msf.740-742.161
|View full text |Cite
|
Sign up to set email alerts
|

Study of Carbonization Process on Surface of Si Substrate in High Vacuum Region with Hydrocarbon Gas

Abstract: The formation mechanism of a carbonized layer was investigated under low-pressure and low-temperature process conditions. The initial carbonized layer under those conditions was formed epitaxially using the silicon atoms sublimated from substrate and the carbon atoms of the gas source. This result is suggested from the consideration of pit formation mechanism at the Si/SiC interface. After the initial layer was formed, the carbonized layer grew by the diffusion process of the carbon atoms through the crystal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Figure 1 shows the XTEM images of the sample prepared at the process pressure of 7.8 × 10 -3 Pa (a) and 7.8 × 10 -2 Pa (b). These images indicate that the flat and comparatively thick layer was formed on the silicon substrate by the epitaxial mechanism (a), and the rough and thin layer was obtained by the diffusion mechanism (b).The difference in the thickness of the carbonized layer can be explained by the pressure dependence of the initially formed epitaxial layer [8]. A lot of pits were formed at the interface between the carbonized layer and the Si substrate in sample (a), thought the part without the pits is shown in the XTEM image of fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 1 shows the XTEM images of the sample prepared at the process pressure of 7.8 × 10 -3 Pa (a) and 7.8 × 10 -2 Pa (b). These images indicate that the flat and comparatively thick layer was formed on the silicon substrate by the epitaxial mechanism (a), and the rough and thin layer was obtained by the diffusion mechanism (b).The difference in the thickness of the carbonized layer can be explained by the pressure dependence of the initially formed epitaxial layer [8]. A lot of pits were formed at the interface between the carbonized layer and the Si substrate in sample (a), thought the part without the pits is shown in the XTEM image of fig.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, it has been shown that the carburization mechanism changes depending on the process condition. In our previous work about the carbonization by C 2 H 4 under the high vacuum condition [8], it was found that these formation mechanisms were changed also with the process pressure. The formation of carbonized layer consists of two different stages.…”
Section: Introductionmentioning
confidence: 98%